Determination of the Schottky barrier height in diodes based on Au–TiB₂–n-SiC 6H from the current-voltage and capacitance-voltage characteristics - Kudryk, Ya.Ya.; Shynkarenko, V.V.; Slipokurov, V.S.; Bigun, R.I.; Kudryk, R.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
We present the results of investigation of the barrier height and ideality factor in Schottky barrier diodes based on Au–TiB₂–n-SiC 6H relying on measuring the current-voltage and capacitance-voltage characteristics. Improving the accuracy of the methods that take into account the effect of the series resistance in calculating the ideality factor and barrier height has been shown with the Cheung method and direct approximation one. It has been ascertained that an inconsistency between real currentvoltage characteristics and its model – the temperature dependence of the barrier height, the ideality factor dependence on the voltage – introduces the basic error into the calculated parameters in the diode under study.